On the need for metaphysics in psychedelic therapy and research - Sjöstedt-Hughes, Peter (Frontiers in Psychology, 2023)
The essential proposal of this text is that psychedelic-induced metaphysical experiences should be integrated and evaluated with recourse to metaphysics. It will be argued that there is a potential extra benefit to patients in psychedelic-assisted therapy if they are provided with an optional, additional, and intelligible schema and discussion of metaphysical options at the integrative phase of the therapy. This schema (the “Metaphysics Matrix”) and a new Metaphysics Matrix Questionnaire (“MMQ”) stemming therefrom will be presented, the latter of which can also be used as an alternative or additional tool for quantitative measurement of psychedelic experience in trials. Metaphysics is not mysticism, despite some overlap; and certainly not all psychedelic experience is metaphysical or mystical—all three terms will be defined and contrasted. Thereafter psychedelic therapy will be presented and analysed in order to reveal the missing place for metaphysics. Metaphysics, with epistemology (theory of knowledge) and axiology (ethics and aesthetics), is a defining branch of Philosophy. Metaphysics, in contrast to mysticism, is considered to be based on argument rather than pure revelation. Thus, in psychedelic-assisted psychotherapy one sees here the potential bridge between reason-based philosophy and practical therapy—or, more broadly, with psychedelic-assisted psychotherapy there is the potential and mutually beneficial fusion of philosophy with practical science.